Reports from behind the “Red Curtain.” Experiencing the Border in Soviet Russia: Antoni Słonimski, Moja podróż do Rosji (1932) and Ante Ciliga U zemlji velike laži (1938) - Szperlik, Ewa (Poznańskie Studia Slawistyczne, 2025)
This article presents a comparative analysis of the personal experiences and impressions of 1930s Russia, as recounted by two figures: A. Słonimski, the Polish poet, editor, and founder of the influential literary group “Skamander,” and A. Ciliga, a Croatian writer and former communist. Ciliga, an unruly Istrian, arrives in the “paradise of socialist progress” as a privileged foreign communist intellectual and university lecturer, only to end up imprisoned in the infamous Gulag system. In contrast, Słonimski, a customer of the state-run tourism agency Intourist and a journalist, travels across the Soviet Union, observing the inner workings of the Stalinist state and the pervasive taboos that shaped its atmosphere. Both autobiographical accounts offer valuable insights into the broader European context of the time. The experience of crossing borders – whether between capitalist and socialist societies, Western and Eastern Europe, or Europe and Asia – shapes the landscape, cities, and mentalities of the inhabitants in profound ways.